Patient Satisfaction and Associated Factors among Outpatient Health Service Users at Primary Hospitals of North Gondar, Northwest Ethiopia, 2016 - Gojjam Eshetie; Amsalu Feleke; Muluken Genetu (Hindawi Limited, 2020)
Introduction. Patient satisfaction with seeking health services is considered as one of the necessary outcomes of health system and measures of health service quality which is directly linked with utilization of the services. The results of this study were crucial and identified important findings for intervention by decision makers on critical need for patient satisfaction improvement as well as to provide evidence for stakeholders in improving quality of outpatient services. This study was aimed at assessing patient satisfaction and associated factors among outpatient health service users at primary hospitals of North Gondar, Northwest Ethiopia. Methods. Facility based cross-sectional study design was conducted in North Gondar from February to March, 2016, among outpatient health service users. Systematic sampling technique was used to get a total of 413 samples. A pretested structured interviewer administered questionnaire was used for data collection. The data were entered to Epi Info version 3.5.1 and exported to SPSS version 20 for analysis. Bivariable and multivariable logistic regression analysis were used to control cofounders and variables with p-value less than 0.05 at 95% CI were considered as significant. Result. This study showed that the overall patient satisfaction was found to be 56.1% at 95% CI (51.0-61.3). Out of all respondents, 218 (53.45%) were males and 130 (31.9%) of respondents were in the age group of ≥45 years. Availability of drugs within the hospitals, patient waiting time at registration room, waiting time to see a doctor after registration, and consulting on treatment options were found to be significantly associated with patient satisfaction. Conclusion. The overall patient satisfaction at North Gondar primary hospitals was rated low as compared to national figures. Hospital management bodies and health care service providers should give attention to improvement of drugs availability and reducing waiting time at registration room and the time length to see a doctor after registration in order to improve patients' satisfaction.